An Analysis of GHG Emissions from Taiwan’s Industrial Sector - Sheng-Hsiung Chiu (International Journal of Automation and Smart Technology, 2015)
To comprehensively elucidate the intelligent automation (IA) demands of Taiwanese companies in Southern China, the researchers administered a structured questionnaire to Taiwanese companies invested in Dongguan region, which was one of the earliest regions to undergo economic reform. A total of 30 valid questionnaires were recovered. Research findings showed that most responders are medium- and large-sized enterprises with production plants in Mainland China. The research also revealed that the higher levels of IA are in the processing, assembly, securing (e.g., tightening screws/fixtures), and quality assurance processes under the category “Manufacturing”, and the hardware connection (connecting computer and equipment) and software integration (i.e., MIS, MES, and ERP, among others) processes under “System Integration”. The majority of these processes possess corresponding mature solutions. The core issues are maintaining production flexibility and reducing payback periods.